GOAL ORIENTATION DAN SUBJECTIVE WELL BEING PADA LANSIA - Desiningrum, Dinie Ratri (Jurnal Psikologi, 2016)
This study aimed to examine the relationship between goal orientation and subjective well-being in the elderly, which includes psychological well-being, emotional well-being and social well-being. The research subjects consisted of 90 elderly from the elderly group Adi Yuswo and Wulandaru Semarang obtained through simple random sampling. The data were obtained using a measuring instrument goal orientation (18 items, Î± = .87), psychological well-being (33 items, Î± = .92), social well-being (33 items, Î± = .93), and emotional well-being (18 items, Î± = .95). Measurements were made using Structural Equation Modelling (SEM) with Linear Structural Relations program (lisrel) 8.80. The analysis showed that the model of goal orientation influence on subjective well being appropriate to the research subject. Subject used their own goal orientation to acquire information, knowledge, insight and new experiences through the association that they follow (knowledge related goal) in addition to obtaining emotional well being. Goal orientation then significant influence to form an overall positive evaluation of the self (subjective well-being), particularly to emerge social acceptance and social actualization (social well being) in individuals aside form the psychological well being and emotional well being.